Nomogram to predict rectal toxicity following prostate cancer radiotherapy - Delobel, Jean-Bernard; Gnep, Khemara; Ospina, Juan David; Beckendorf, Véronique; Chira, Ciprian; Zhu, Jian; Bossi, Alberto; Messai, Taha; Acosta, Oscar; Castelli, Joël; de Crevoisier, Renaud (PLOS ONE, 2017)
Background To identify predictors of acute and late rectal toxicity following prostate cancer radiotherapy (RT), while integrating the potential impact of RT technique, dose escalation, and moderate hypofractionation, thus enabling us to generate a nomogram for individual prediction. Methods In total, 972 patients underwent RT for localized prostate cancer, to a total dose of 70 Gy or 80 Gy, using two different fractionations (2 Gy or 2.5 Gy/day), by means of several RT techniques (3D conformal RT [3DCRT], intensity-modulated RT [IMRT], or image-guided RT [IGRT]). Multivariate analyses were performed to identify predictors of acute and late rectal toxicity. A nomogram was generated based on the logistic regression model used to predict the 3-year rectal toxicity risk, with its accuracy assessed by dividing the cohort into training and validation subgroups. Results Mean follow-up for the entire cohort was 62 months, ranging from 6 to 235. The rate of acute Grade ≥2 rectal toxicity was 22.2%, decreasing when combining IMRT and IGRT, compared to 3DCRT (RR = 0.4, 95%CI: 0.3–0.6, p<0.01). The 5-year Grade ≥2 risks for rectal bleeding, urgency/tenesmus, diarrhea, and fecal incontinence were 9.9%, 4.5%, 2.8%, and 0.4%, respectively. The 3-year Grade ≥2 risk for overall rectal toxicity increased with total dose (p<0.01, RR = 1.1, 95%CI: 1.0–1.1) and dose per fraction (2Gy vs. 2.5Gy) (p = 0.03, RR = 3.3, 95%CI: 1.1–10.0), and decreased when combining IMRT and IGRT (RR = 0.50, 95% CI: 0.3–0.8, p<0.01). Based on these three parameters, a nomogram was generated. Conclusions Dose escalation and moderate hypofractionation increase late rectal toxicity. IMRT combined with IGRT markedly decreases acute and late rectal toxicity. Performing combined IMRT and IGRT can thus be envisaged for dose escalation and moderate hypofractionation. Our nomogram predicts the 3-year rectal toxicity risk by integrating total dose, fraction dose, and RT technique.